Eksplorasi Pengalaman Pembelajaran Daring Pada Masa Pandemi COVID-19 (Studi Kasus: Mahasiswa SAP Sistem Informasi Angkatan 2019 Fakultas Ilmu Komputer Universitas Brawijaya) - Risky Danamonika Pratiwi; Diah Priharsari; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The beginning of the Covid-19 pandemic occurred when the spread of the corona virus entered the Wuhan area, China. After China, the spread of the virus was followed by several other countries including Indonesia. This virus has had an impact on the education sector in Indonesia. The education sector is responsive to preventing the spread of the virus by conducting online learning. Online learning is carried out from elementary to tertiary level. The purpose of this research is to find out what experiences, students get during the online learning process. To get information about student experiences, researchers explored the factors of the problems faced, activities liked and activities disliked by students. These issues focus on information systems, where it is not only technology, but how it influences the surrounding environment and students in running technology during online learning. The exploration was carried out by collecting data using the semi-structured interview method. Interviews were conducted on SAP Information System students class 2019, Faculty of Computer Science, Brawijaya University. The interview involved 13 students with the number determined by the saturation of the data. The data are processed using thematic coding analysis using the Atlas.ti application. The findings of this study provide suggestions for improving the factors that affect the online learning experience from every aspect found so that learning can run well. The suggestions given are based on the results of data analysis from the likes and dislikes experience obtained during the online learning process. These suggestions are made for all stakeholders so that there will be further improvements to the online learning process.